Manajemen Pengelolaan BUMDes Sejahtera Desa Air Satan - Kusnadi Yudha Wiguna; Ryan Oktavianie; Anggia Syafitri; Yayuk Marliza; Tiara Febriyanti; Fredy Andito; Indah Pramudya (JURNAL BESEMAH : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
This mentoring activity aims to make the community able to understand and practise BUMDes management activities; besides, the community is trained on how to manage BUMDes so that they get funds in accordance with what has been invested. The methods in this activity are observation, survey, preparation of a work program, implementation of activities, coordination with related parties, and implementation of activities. This community service activity can increase knowledge and insight about the management of BUMDes and the preparation of BUMDes financial reports in accordance with generally accepted financial accounting standards in the village of Air Satan, Muara Beliti District, Musi Rawas Regency. The series of socialisation and training activities were well attended by village officials, BUMDes operational managers, and the Air Satan Village Community. The BUMDes management assistance activities are followed and understood by the operational managers of BUMDes Prosperous because the mentoring method is adapted to the characteristics of BUMDes participants and administrators that have been previously analyzed.